2021
DOI: 10.1186/s42834-021-00099-3
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and measurement of air quality in the traffic congestion area

Abstract: The traffic congestion in the Hsuehshan tunnel and at the Toucheng interchange has led to traffic-related air pollution with increasing concern. To ensure the authenticity of our simulation, the concentration of the last 150 m in Hsuehshan tunnel was simulated using the computational fluid dynamics fluid model. The air quality at the Toucheng interchange along a 2 km length highway was simulated using the California Line Source Dispersion Model. The differences in air quality between rush hours and normal traf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…These model performance evaluation indicators were all close to the ideal values (NMSE and FB = 0.0) [51]. The results were comparable to previously reported PM levels due to road traffic activities, simulated using a line source dispersion model, CALINE 4 (NMSE = 0.08 and FB = −0.01) [52], and a Lagrangian particle model, (GRAL) (NMSE = 0.04 and FB = 0.13) [53]. The simulation performance in our study is better than the performance reported in previous work using the WinOSPM, ADMS-Urban, and AEOLIUS models (in which NMSE ranged from 0.11 to 0.23 and FB ranged from −0.08 to 0.26) [54].…”
Section: Evaluation Of R-linesupporting
confidence: 86%
“…These model performance evaluation indicators were all close to the ideal values (NMSE and FB = 0.0) [51]. The results were comparable to previously reported PM levels due to road traffic activities, simulated using a line source dispersion model, CALINE 4 (NMSE = 0.08 and FB = −0.01) [52], and a Lagrangian particle model, (GRAL) (NMSE = 0.04 and FB = 0.13) [53]. The simulation performance in our study is better than the performance reported in previous work using the WinOSPM, ADMS-Urban, and AEOLIUS models (in which NMSE ranged from 0.11 to 0.23 and FB ranged from −0.08 to 0.26) [54].…”
Section: Evaluation Of R-linesupporting
confidence: 86%
“…Another novel application of LCPMS was in measuring the three-dimensional distribution of air pollutants aboard a drone. This setup was used to measure the three-dimensional distribution of PM 2.5 concentrations along a tunnel in Taiwan using two kinds of sensors previously calibrated against Taiwan EPA instruments [50]. The measurements were also used to validate the results of CALINE4 simulations that were aimed at providing air quality forecasts for the area.…”
Section: Transportationmentioning
confidence: 99%
“…High values of BC, OC, and K are indicators of BB (Lestari and Mauliadi, 2009). (Yu et al, 2021), SA, and SD, in contrast to the PM2.5 source contributions obtained without the OC data.…”
Section: Accepted Manuscriptmentioning
confidence: 61%